2020
DOI: 10.1073/pnas.2018562117
|View full text |Cite
|
Sign up to set email alerts
|

Correction for Yang et al., Accumulation of high-value bioproducts in planta can improve the economics of advanced biofuels

Abstract: The authors note that on page 8647, right column, first full paragraph, lines 1-2, "Biorefinery plant life is assumed to be 30 years, with the internal rate of return of 10%" should instead appear as "Biorefinery plant life is assumed to be 30 years, with the internal rate of return of 15%." The authors note that Table S2 in the SI Appendix, which includes the internal rate of return ("Interest rate") as a parameter for sensitivity analysis, appeared incorrectly. The SI Appendix has been corrected online.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Biddy et al [ 141 ], demonstrated the potential of increasing succinic acid production by four-fold reduced the price significantly [ 143 ]. The demand for some specialty chemicals would be satisfied by just 5–10 biorefineries and a few biorefineries could satisfy the needs of the high-value pharmaceutical markets [ 144 ]. Expanding the market size by considering derivative chemicals is vital.…”
Section: Contributions Of Food Wastes For Bioeconomymentioning
confidence: 99%
“…Biddy et al [ 141 ], demonstrated the potential of increasing succinic acid production by four-fold reduced the price significantly [ 143 ]. The demand for some specialty chemicals would be satisfied by just 5–10 biorefineries and a few biorefineries could satisfy the needs of the high-value pharmaceutical markets [ 144 ]. Expanding the market size by considering derivative chemicals is vital.…”
Section: Contributions Of Food Wastes For Bioeconomymentioning
confidence: 99%